2019
DOI: 10.1093/jbcr/irz060
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic Profile of Burn Wounds at a Tertiary Government Hospital in the Philippines—UP-PGH ATR Burn Center

Abstract: Wound infection is a major cause of morbidity and mortality among burn patients. Recent changes in the epidemiology of burn wound infections were observed due to the steady rise of drug-resistant bacteria. The objective of this study is to determine the most common burn wound pathogens isolated among patients admitted at the UP-PGH ATR Burn Center, describe their respective susceptibility patterns, and calculate incidence rates of burn wound colonization, local, and invasive infection. Patients admitted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
3
1
0
1
Order By: Relevance
“…Additionally, there was an obvious increase in the carbapenem-resistant and methicillin-resistant organisms, consistent with other studies [ 13 , 16 , 17 ]. Notably, a 10-year retrospective study in Turkey showed a decrease in carbapenem resistance form Pseudomonas aeruginosa although that in Acinetobacter baumannii increased to 94%, over time [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, there was an obvious increase in the carbapenem-resistant and methicillin-resistant organisms, consistent with other studies [ 13 , 16 , 17 ]. Notably, a 10-year retrospective study in Turkey showed a decrease in carbapenem resistance form Pseudomonas aeruginosa although that in Acinetobacter baumannii increased to 94%, over time [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports showed that the burn wound was typically colonized with Gram-positive bacteria within 2 days while Gram-negative bacteria colonized the wound after 2–3 days [ 7 , 12 ], similar to observations from the present study. Additionally, the most isolated organisms were Gram-negative bacteria, corroborating with previous studies [ 11 , 13 ]. However, Stenotrophomonas maltophilia was shown to be one of the most common Gram-negative organisms, contrary to previous findings [ 7 , 14 ] which reported that Acinetobacter baumannii was the predominant Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Burn wounds are especially sensitive to infection for several reasons. Destruction of the epidermal barrier in combination with denaturation of proteins and lipids creates a favorable medium for microbial growth [ 36 , 37 ]. Since it is impossible to make the required concentration of the systemically introduced antibiotics into the damaged tissues with impaired blood circulation, local application of antimicrobial preparations becomes ever more vital [ 38 , 39 ].…”
Section: Antibiotic Resistance Of Microflora In Burnsmentioning
confidence: 99%
“…ten in einer Analyse auf einer niederländischen Brandverletzten-Intensivstation über 7 Jahre hinweg(2005- 2011) bei Wundabstrichen Staphylococcus aureus als häufigsten Erreger und die Zunahme resistenter gramnegativer Bakterien (nicht signifikant)[12]. Abesamis et al untersuchten in einer Studie das bakte-riologische Profil von Verbrennungswunden in einem Brandverletztenzentrum der Philippinen[13].ESKAPEDie häufigsten Erreger auf Verbrennungswunden gehören somit zu den ESKAPE-Pathogenen (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa und Enterobacter-Spezies). Aufgrund ihrer Fähigkeiten, besonders ausgeprägte Antibiotikaresistenzen auszubilden, werden die therapeutischen Möglichkeiten knapp.…”
unclassified